Analyzing public basic education teachers paradigm shifts in teaching as aftermath of the LEEP Training Program - De Gracia, Victor G. (Animo Repository, 2017)
This descriptive qualitative study looked into the changes in the paradigm of teaching among teacher trainees of the LEEP training program conducted on June 20-21, 2013 and August 21-22, 2015 in the Division of Guimaras, Philippines. This responded to the need of the Department of Education to document evidences in the field on the changes in pedagogy as a result of the implementation of the K to 12 program and the development of 21st century learners. Data were gathered through exhaustive interview with eighteen (18) exemplar teachers coming from both elementary and secondary schools of the ten (10) districts of Guimaras. Significant responses which reflected their experiences both before and after LEEP training were coded and organized into a matrix. The descriptive qualitative research design was used to describe the phenomenon of paradigm shift in teaching among the teacher trainees. The data were analyzed using the the seven (7)-point LEEP sequence was considered. The sequence was categorized into three (3) components, namely formulating learning outcomes, assessing learning outcomes, and designing learning activities. Results revealed that LEEP training made the teachers learner-centered in their teaching and developed in them the initiative to explore ways and means to ensure that their learners were actively engaged in their learning. The paradigm shift in teaching experienced by teachers who have undergone the LEEP training is described as a change in behavior in terms of students response, teacher provisions, and teachers learning perspectives. This shift in pedagogy is most needed for 21st century learning.